1996
DOI: 10.1016/s0195-5616(96)50108-7
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocephalus

Abstract: Hydrocephalus may be an acquired or congenital condition. Clinical signs often reflect the level of brain involvement. In young dogs, the presence of a dome-shaped head and/or persistent fontanel are suggestive of hydrocephalus. Ventriculoperitoneal shunting is often used for definitive treatment of hydrocephalus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
64
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 20 publications
1
64
1
Order By: Relevance
“…The syringomyelia in the 4 present cases may have been produced by the mechanism reported by Milhorat et al [15]. It has been reported that FIP is a common infectious dis- ease causing feline hydrocephalus [7]. Hydrocephalus has been reported to form due to the accumulation of inflammatory cells at sites of narrowing along the CSF pathway [16].…”
mentioning
confidence: 77%
“…The syringomyelia in the 4 present cases may have been produced by the mechanism reported by Milhorat et al [15]. It has been reported that FIP is a common infectious dis- ease causing feline hydrocephalus [7]. Hydrocephalus has been reported to form due to the accumulation of inflammatory cells at sites of narrowing along the CSF pathway [16].…”
mentioning
confidence: 77%
“…Moreover, it has been reported that FIP is a common infectious disease causing feline hydrocephalus [7]. In this case, enlargement of the ventricles was detected and the margin of the brainstem and fourth ventricle were enhanced in the contrast-T1 weighted images.…”
mentioning
confidence: 61%
“…One study of hydrocephalus revealed a success rate range of improving clinical signs ranging from 50% to 90% in dogs that had undergone ventriculoperitoneal shunting. VP shunt systems have three required components: a ventricular catheter, siphone control mechanism, and distal catheter (Harrington and Moore, 1996). There are two approaches of placing the ventricular catheter in the frontal horn: anterior placement and posterior placement.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of treatment is generally based on physical status, age, and the cause of hydrocephalus (Harrington and Moore, 1996). Usually, medical treatments such as diuretics and glucocorticoids are applied to the animal to decrease CSF volume before surgical treatment (Coates and Axlund, 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation